Localization and movement of Tregs in gastrointestinal tract: a systematic review - Yosuke Harada; Kentaro Miyamoto; Akihiko Chida; Anna Tojo Okuzawa; Yusuke Yoshimatsu; Yumi Kudo; Tomohisa Sujino (BMC, 2022)
Abstract Background The intestine is rich in food-derived and microbe-derived antigens. Regulatory T cells (Tregs) are an essential T-cell population that prevents systemic autoimmune diseases and inhibits inflammation by encountering antigens. Previously, it was reported that the functional loss of Tregs induces systemic inflammation, including inflammatory bowel disease and graft-versus-host disease in human and murine models. However, there is a dearth of information about how Tregs localize in different tissues and suppress effector cells. Main body The development of Tregs and their molecular mechanism in the digestive tract have been elucidated earlier using murine genetic models, infectious models, and human samples. Tregs suppress immune and other nonimmune cells through direct effect and cytokine production. The recent development of in vivo imaging technology allows us to visualize how Tregs localize and move in the settings of inflammation and homeostasis. This is important because, according to a recent report, Treg characterization and function are regulated by their location. Tregs located in the proximal intestine and its draining lymph nodes induce tolerance against food antigens, and those located in the distal intestine suppress the inflammation induced by microbial antigens. Taken together, various Tregs are induced in a location-specific manner in the gastrointestinal tract and influence the homeostasis of the gut. Conclusion In this review, we summarize how Tregs are induced in the digestive tract and the application of in vivo Treg imaging to elucidate immune homeostasis in the digestive tract.